PERKEMBANGAN PESERTA DIDIK FASE DEWASA DALAM PROSES PEMBELAJARAN PADA LEVEL PERGURUAN TINGGI - Zihar, Nabitaelfa (Prodi Pendidikan Agama Islam STAIN Mandailing Natal, 2024)
The learning process is an interaction activity between teachers and students. Students as the center of education are required to be more active in teaching and learning activities, one of which is by responding to the material presented by the teacher. In the adult phase, the development of students in the learning process goes through an ups and downs phase, which often creates an imbalance. Therefore, researchers conducted a study that aims to find out what developments appear in the adult phase of students. Given that the relationship between lecturers and students is very closely related, lecturers and students must be able to understand each other to achieve the goals that have been designed at the beginning of the semester. This study uses descriptive quantitative research methods, using the questionnaire method as a method of data collection.